PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI ZAT ADITIF - Senja, Andhini Muthia; Fauziah, An Nuril Maulida (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2023)
This research aimed to determine the problem based learning implementation model toward students' critical thinking skills on the material of additives. This research used pre-experimental design with one group pretest posttest. The subjects’ in this research were 31 students’ of VIII B class in Public Junior High School 27 Gresik. Data collection technique of pretest and posttest, observation, and provision of questionnaires. The data was analyzed quantitatively. The results of the N-Gain calculation showed that the application of problem based learning model increased students' critical thinking skills on the additives material with a high category. Descriptive analysis on learning activities by the given treatment had a high percentage result. The conclusion obtained was science learning using a problem based learning model on the additives material can improve students’ critical thinking skills.